2024
DOI: 10.3390/nano14010110
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Zr-Based UiO-66 Metal–Organic Frameworks in Basic Solutions

Jun Yeong Kim,
Jiwon Kang,
Seungheon Cha
et al.

Abstract: Although Zr-based metal–organic frameworks (MOFs) exhibit robust chemical and physical stability in the presence of moisture and acidic conditions, their susceptibility to nucleophilic attacks from bases poses a critical challenge to their overall stability. Herein, we systematically investigate the stability of Zr-based UiO-66 (UiO = University of Oslo) MOFs in basic solutions. The impact of 11 standard bases, including inorganic salts and organic bases, on the stability of these MOFs is examined. The destruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Figure demonstrates the 1 H NMR characterization of the prepared UiO-66 after digestion with NaOD/D 2 O. The peaks of UiO-66 show a signal at 7.48 ppm attributed to the BDC structure of the ligands . NMR analysis of the other functionalized UiO-66 displays three signals related to the hydroxyterephthalic acid and nitroterephthalic acid linkers in UiO-66-OH and UiO-66-NO 2 , respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure demonstrates the 1 H NMR characterization of the prepared UiO-66 after digestion with NaOD/D 2 O. The peaks of UiO-66 show a signal at 7.48 ppm attributed to the BDC structure of the ligands . NMR analysis of the other functionalized UiO-66 displays three signals related to the hydroxyterephthalic acid and nitroterephthalic acid linkers in UiO-66-OH and UiO-66-NO 2 , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The peaks of UiO-66 show a signal at 7.48 ppm attributed to the BDC structure of the ligands. 42 NMR analysis of the other functionalized UiO-66 displays three signals related to the hydroxyterephthalic acid and nitroterephthalic acid linkers in UiO-66-OH and UiO-66-NO 2 , respectively. The integrations of the NMR peaks for UiO-66 are illustrated in Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Many of the stability studies in aqueous media that were presented in the literature are based on a post-exposure analysis of the corresponding solids using powder X-ray diffraction (XRPD), gas adsorption, scanning electron microscopy (SEM), infrared spectroscopy (FTIR), or their combination with computational methods. 26,32,45,46,48–53 For example, when MOFs’ stability is inferred from XRPD patterns before and after the treatment, while ignoring the mass balance, presence of an amorphous phase, and changes in the chemical composition, erroneous conclusions can be drawn. In our recent studies, we have demonstrated that the structure of UiO-66, a Zr-based MOF considered one of the most stable MOFs, is compromised already at neutral pH or in the presence of commonly used buffers, such as TRIS or phosphate-buffered saline.…”
Section: Introductionmentioning
confidence: 99%